Tripartite relationships between frontline managers’ competencies, wellbeing initiatives, and perceived job engagement in a developing economy - Falola, Hezekiah; Joel, Opeyemi; Efe-Imafidon, Emmanuel; Onyia, Valerie (International Journal of Innovative Research and Scientific Studies, 2024)
The main objective of this study is to investigate the tripartite relationships between frontline managers' competencies, wellbeing initiatives, and perceived job engagement in some selected manufacturing firms in Nigeria. Based on a sample size of four hundred and ninety-nine (499) frontline managers drawn from selected manufacturing firms, smart partial least squares (SMART PLS) 3.0 was adopted to show the relationships among frontline managers' competencies, wellbeing initiatives, and perceived job engagement in the world of work. The statistical results show that the dimensions of front-line managers' competencies, significant change-management skills, employee relations, business savvy, and problem-solving skills, greatly influenced job engagement, while components of talent wellbeing initiatives mediate the relationship between front-line managers' competencies and job engagement. The study recommends that frontline managers adopt a continuous competency evaluation approach, focusing on frequent evaluations to identify areas of improvement and potential for development. As a means of developing a resilient and competent managerial workforce, it emphasises the significance of specifically designed wellbeing programmes that address the difficulties associated with their jobs. Organisations may foster a good work environment that improves wellbeing in general and supports long-term, productive engagement. Existing literature that focused on the frontline managers' competency theme in the manufacturing industry scarcely examined the processes critical to wellbeing initiatives and perceived job engagement in the manufacturing industry. As a result, the present study uses a moderating variable of employee wellbeing initiatives to explain how frontline managers’ competencies foster job engagement.